Development Status of Low-Grade Magnesite Beneficiation Technology - Yin, Yufei (International Journal of Materials Science and Technology Studies, 2024)
Magnesite is a non-metallic mineral rich in magnesium. Due to its excellent fire resistance, it is widely used in the manufacture of magnesia-carbon bricks, magnesia and other refractory materials, which are widely used in various fields such as chemical industry and metallurgy. Due to the uneven distribution of magnesite resources and the reduction of high-quality magnesite resources caused by large-scale mining, the selection of low-grade magnesite has become a key problem of magnesium resources. The lower grade ores are abandoned because they contain a large amount of impurities and do not meet the requirements of industrial production, which leads to the unreasonable utilization of magnesite resources. This paper summarizes the current status of low-grade magnesite separation technology and flotation reagent development in China, and gives some suggestions on the development of low-grade magnesite beneficiation technology, aiming at providing certain theory and reference value for magnesite beneficiation.